Skin Acute Wound Healing: A Comprehensive Review - Luis Cañedo-Dorantes; Mara Cañedo-Ayala (International Journal of Inflammation)
Experimental work of the last two decades has revealed the general steps of the wound healing process. This complex network has been organized in three sequential and overlapping steps. The first step of the inflammatory phase is an immediate response to injury; primary sensory neurons sense injury and send danger signals to the brain, to stop bleeding and start inflammation. The following target of the inflammatory phase, led by the peripheral blood mononuclear cells, is to eliminate the pathogens and clean the wound. Once this is completed, the inflammatory phase is resolved and homeostasis is restored. The aim of the proliferative phase, the second phase, is to repair wound damage and begin tissue remodeling. Fibroplasia, reepithelialization, angiogenesis, and peripheral nerve repair are the central actions of this phase. Lastly, the objective of the final phase is to complete tissue remodeling and restore skin integrity. This review provides present day information regarding the status of the participant cells, extracellular matrix, cytokines, chemokines, and growth factors, as well as their interactions with the microenvironment during the wound healing process.